Determinants of economic growth: will data tell? - Antonio Ciccone; Marek Jarociński (European Central Bank (ECB), 2008)
Many factors inhibiting and facilitating economic growth have been suggested. Will international income data tell which matter when all are treated symmetrically a priori? We find that growth determinants emerging from agnostic Bayesian model averaging and classical model selection procedures are sensitive to income differences across datasets. For example, many of the 1975-1996 growth determinants according to World Bank income data turn out to be irrelevant when using Penn World Table data instead (the WB adjusts for purchasing power using a slightly different methodology). And each revision of the 1960-1996 PWT income data brings substantial changes regarding growth determinants. We show that research based on stronger priors about potential growth determinants is more robust to imperfect international income data.
Keywords: E01; O47; 330; Growth regressions; robust growth determinants; Wirtschaftswachstum; Internationale Wirtschaft; Vergleich; Datenqualität; Einkommen; Statistik; Theorie; Bayes-Statistik